2021
DOI: 10.22435/mpk.v31i1.3521
|View full text |Cite
|
Sign up to set email alerts
|

Determinan Stres Kerja pada Aparatur Sipil Negara Dinas Pendidikan Kota Cilegon Saat Work From Home di Era Pandemi COVID-19 Tahun 2020

Abstract: Work stress is a serious problem that results in a emotional mental disorder rate of 9.8% in Indonesia. State civil apparatus (ASN) is a group of workers who are at risk of experiencing work stress. Work stress is caused by employees who perform the work from home (WFH) system, so that employees feel pressured and have an excessive workload on adjusting changes in the learning system in schools due to COVID-19. This study aimed to find the determinant of work stress on the ASN at Departmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…Data from riskesdas for DKI Jakarta also increased from 2013 by 8% to 10% in 2018. The percentage increase exceeds the percentage of Indonesia's national stress rate (Azhar and Iriani 2021).…”
Section: Introductionmentioning
confidence: 84%
“…Data from riskesdas for DKI Jakarta also increased from 2013 by 8% to 10% in 2018. The percentage increase exceeds the percentage of Indonesia's national stress rate (Azhar and Iriani 2021).…”
Section: Introductionmentioning
confidence: 84%
“…The Covid-19 pandemic also caused increased occupational stress for employees (Ibrahim & Suhariadi, 2021). This statement was supported by Azhar and Iriani (2020), showing that occupational stress in the Civil Servant (ASN) was one of them. It was caused by employees who carried out a work from home (WFH) system during the Covid-19 pandemic, causing excessive work pressure and workload with adjustments to changes in the work system.…”
Section: Mohamad Rizal Dina Syakina Employees' Emotional Intelligence...mentioning
confidence: 92%
“…The same is felt by the state civil apparatus (ASN) who work in government institutions. Azhar & Iriani [3] found that ASN in the education office was seriously affected by this condition. As a government institution responsible for public services in education, ASN in the education office may experience increased pressure and burden on these adjustments.…”
Section: Introductionmentioning
confidence: 99%
“…As a government institution responsible for public services in education, ASN in the education office may experience increased pressure and burden on these adjustments. Azhar & Iriani [3] found that more than 30% of education office employees experienced severe to very severe stress. This condition is closely influenced by the work environment, such as job demands [4], social support, interpersonal relationships, and organizational changes [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation